Penggunaan Makrozoobentos Sebagai Indikator Status Perairan Hulu Sungai Cisadane, Bogor - Dyah Muji Rahayu; Gunawan Pratama Yoga; Hefni Effendi; Yusli Wardiatno (Institut Pertanian Bogor, 2015)
Anthropogenic pollution (organic matter and Hg) around Cisadane River upstream can affect the abundances of macrozoobenthos. The aim of this research was to identify the abundances of macrozoobenthos and feeding groups, and also to identify the status of waters based on macrozoobenthos community. The research was conducted on January to March in four locations in the upstream of Cisadane River, covering Cikuluwung (ST 1), Cisarua (ST 2), Curug Bitung (ST 3), and Lukut (ST 4). Samples were collected with kick net and Eckman Grab. The dominance macrozoobenthos are Bungona (171 ind/m2), Simulium (101 ind/m2), Cheumatopsyche (50 ind/m2), and Polypedilum (28 ind/m2). Based on feeding groups, the dominance are filtering collector and gatherer collector. Based on the Pollution Index and Heavy Metal Pollution Index (Hg) on sediment, the upstream of Cisadane River is low polluted whereas EPT Index and Signal showed that upstream of Cisadane River is moderate polluted.